Adult neural stem cells mediate hippocampal synapse elimination for circuit homeostasis through MERTK - Dezhe Qin; Qiang Liu; Ziqi Liang; Hui Cai; Xing Luo; Min Wang; Weixiang Guo (Proceedings of the National Academy of Sciences, 2026)
Although radial-like neural stem cells (rNSCs) give rise to functional neurons throughout life in discrete regions of the adult brain, their functions are not limited to neurogenesis. Recent studies indicate that the processes of rNSCs approach and/or wrap synapses. However, the function of these processes at synapses remains unknown. In this study, we report a role for rNSCs in actively engulfing synapses in the adult hippocampus. Mice in which rNSCs lack the phagocytic receptor MERTK exhibit reduced elimination of excitatory synapses, defective synaptic plasticity, and impaired formation of hippocampal learning and memory, but normal neurogenesis. Furthermore, we show that MERTK-dependent phagocytosis of excitatory synapses by rNSCs contributes to voluntary exercise-induced cognitive enhancements. Together, our data suggest that rNSCs eliminate unnecessary excitatory synaptic connections in the adult hippocampus through MERTK, thereby maintaining circuit connectivity and cognitive function independently of neurogenesis.